GRACE-derived ice-mass loss spread over Greenland - Nahavandchi H.; Joodaki G.; Schwarz V. (Journal of Geodetic Science, 2015)
The Gravity Recovery and Climate Experiment (GRACE) monthly satellite data is used to examine the extent and magnitude of Greenland ice sheet melting for 2003-2012. We show that the well documented Greenland ice mass loss in the southern region spread to northwest Greenland in the period from2007 to 2010 and 2010 to 2012 by estimating ice mass variability over time in Greenland. The ice-mass melting is estimated to –183±11 Gt/yr. This estimation means that Greenland is still losing much more ice than gained, and continuing to contribute to global sea level rise in a warming world. Unlike other recent studies, our method employs a non-isotropic filter. A nonisotropic filter is used to decorrelate the GRACE data, since the GRACE noise structure has a non-isotropic nature.